Menjaga Generasi Islam Bangsa untuk Cerdas Membaca Al Qur’an sesuai Tajwid - Mohamad Nasirudin; Salim Ashar; Siti Sulaikho; Dawam Cahya; Sholeh Abdul Baqi (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2021)
The implementation of community service activities in this PPM scheme is expected to provide the best results for the community, TPQ students, the targets subject to the program. The first problem is the knowledge constraints possessed by TPQ students related to the knowledge of recitation. The solution given is through tajwid learning. The approach method for implementing community service activities in this PPM scheme includes providing material, discussion, and practice. The provision of material and discussion was carried out at the beginning of the learning activity and the introduction of the Tajweed media. The material taught in this activity is tajwid material and the nature of the letters and their macros through written form and intensive mentoring until students can read the Qur'an correctly according to their recitation and makhroj. Through this learning activity it is hoped that it can solve the problems faced by parents. This activity aims to see the activeness and skills of teachers in teaching and delivering recitation knowledge. This activity is carried out by assisting the teacher in learning tajwid independently in the classroom. Through observation activities in the classroom, the teacher is very skilled in providing recitation in the classroom. In addition, the learning is also in accordance with the targeted material from the start. The application of this learning shows that students in the class are very enthusiastic and actively interact with the teacher during learning. In addition, this learning can improve students' understanding of recitation.